2000
DOI: 10.1002/1099-0801(200011)14:7<459::aid-bmc7>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Excretion pattern investigation of urinary normal and modified nucleosides of breast cancer patients by RP-HPLC and factor analysis method

Abstract: Modified nucleosides, formed post-transcriptionally in RNA by a number of modification enzymes, are excreted in abnormal levels in the urine of patients with malignant tumors. To test their usefulness as tumor markers, and to compare them with the conventional tumor markers, a reversed-phase high-performance liquid chromatographic (RP-HPLC) method and a factor analysis method have been used to study the excretion pattern of nucleosides of breast cancer patients. A clear cut differentiation of the breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 14 publications
2
27
0
Order By: Relevance
“…The following seven were the most significant ones: cytidine, N2,N2-dimethylguanine, PCNR, 2-methylguanosine, 1-methylguanosine, pseudouridine and 1-methyladenosine. These nucleosides have already been reported as useful biochemical 'indicators' in malignant diseases (Lakings et al, 1977;Koshida et al, 1985;Holstege et al, 1986;Oerlemans and Lange, 1986;Sander et al, 1986;Rasmuson et al, 1987;Boos et al, 1988;McEntire et al, 1989;Gehrke and Kuo, 1990;Schöch et al, 1990a, b;Kvist et al, 1993;Nakano et al, 1993;Topp et al, 1993;Rasmuson and Björk, 1995;Martinow et al, 1998;Xu et al, 2000;Dudley et al, 2004;Yang et al, 2004;Zheng et al, 2005). Cytidine and uridine were found to be much more increased than reported in other publications.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The following seven were the most significant ones: cytidine, N2,N2-dimethylguanine, PCNR, 2-methylguanosine, 1-methylguanosine, pseudouridine and 1-methyladenosine. These nucleosides have already been reported as useful biochemical 'indicators' in malignant diseases (Lakings et al, 1977;Koshida et al, 1985;Holstege et al, 1986;Oerlemans and Lange, 1986;Sander et al, 1986;Rasmuson et al, 1987;Boos et al, 1988;McEntire et al, 1989;Gehrke and Kuo, 1990;Schöch et al, 1990a, b;Kvist et al, 1993;Nakano et al, 1993;Topp et al, 1993;Rasmuson and Björk, 1995;Martinow et al, 1998;Xu et al, 2000;Dudley et al, 2004;Yang et al, 2004;Zheng et al, 2005). Cytidine and uridine were found to be much more increased than reported in other publications.…”
Section: Discussionmentioning
confidence: 99%
“…Before the samples could be analysed by HPLC, a treatment is necessary to remove the proteins. Other authors reported on using phenyl boronate affinity column for nucleoside isolations (Koshida et al, 1985;Holstege et al, 1986;Oerlemans and Lange, 1986;Sander et al, 1986;Rasmuson et al, 1987;McEntire et al, 1989;Gehrke and Kuo, 1990;Schöch et al, 1990a;Kvist et al, 1993;Nakano et al, 1993;Topp et al, 1993;Rasmuson and Björk, 1995;Martinow et al, 1998;Xu et al, 2000;Yang et al, 2004) or using the Baker SPE system with aromatic sulphonic acid (Schöch et al, 1990b). These fractionation methods of nucleosides from urine were found to be too complex and time consuming to allow the analyses of large numbers of urine samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations